The regulation of investors` influence in German professional football. An analysis of the `50+1 rule` and its future from the perspective of potential investors - Bauers, S. B.; Hovemann, G. (German Journal of Exercise and Sport Research, 2019)
The German Football Association and the German Football League prevent investors from having controlling influences over professional football teams. To compete in the Bundesliga, 2nd Bundesliga, 3rd League, and Regional Leagues, the Verein (non-profit organization) must control the professional football team. This is possible due to the so-called `50 + 1 Rule`. When comparing other top European football leagues, the `50 + 1 Rule` is only being utilized in Germany. However, this rule is being increasingly criticized since it generates limitations on investors` property rights within their professional football team. Some investigations criticize that these limitations on property rights impair investment incentives. Hence, some potential investors possibly have not invested in German football teams in the past. Taking into consideration the criticisms against the `50 + 1 Rule`, this paper serves as an initial investigation on the rule`s impacts from the perspective of potential investors. To empirically weigh and reveal possible investment barriers, potential investors were asked about their opinions on the `50 + 1 Rule` and the rule`s future. Surprisingly, we have identified an advocacy of the rule. This finding illustrates a similarity regarding the perspective of German football clubs, as well as football fans, and a contrast regarding the perspective of current investors. Finally, our current and previous survey results form an important stakeholder-oriented base for discussion in order to assess the future decision regarding the retention or repeal of the `50 + 1 Rule`. Der Deutsche Fußball-Bund und die Deutsche Fußball Liga unterbinden, dass Investoren beherrschenden Einfluss auf ausgegliederte Spielbetriebsgesellschaften ausüben. Sofern eine Spielbetriebsgesellschaft am Spielbetrieb der Bundesliga, 2. Bundesliga, 3. Liga und der Regionalligen teilnehmen möchte, muss der Mutterverein die Kontrolle über die Spielbetriebsgesellschaft selbst innehaben. Ermöglicht wird dies durch die sogenannte 50 + 1-Regel. Ein Vergleich mit anderen Topligen des europäischen Fußballs ergibt, dass diese Regel nur in Deutschland angewendet wird. Die 50 + 1-Regel ist zunehmender Kritik ausgesetzt, da sie die Handlungs- und Verfügungsrechte von Investoren limitiert. In einigen Studien wird kritisiert, dass die Beschränkungen dieser Rechte die Investitionsanreize reduzieren. In der Folge haben manche potenzielle Investoren möglicherweise davon abgesehen, in deutsche Spielbetriebsgesellschaften zu investieren. Unter Berücksichtigung der Kritik liefert der vorliegende Beitrag eine erste Untersuchung zu den Auswirkungen der 50 + 1-Regel aus der Perspektive potenzieller Investoren. Um mögliche Investitionsbarrieren empirisch abzuwägen bzw. aufzudecken, wurden potenzielle Investoren nach ihrer Meinung zur 50+1-Regel und deren Zukunft befragt. Überraschenderweise lässt sich eine Befürwortung der Regel konstatieren. Dieses Ergebnis zeigt eine Gemeinsamkeit mit Blick auf die Perspektive deutscher Fußballklubs wie auch der Fußballfans und einen Gegensatz bezüglich der Perspektive aktueller Investoren. Letztlich bilden unsere vorliegenden und früheren Befragungsergebnisse eine zentrale Diskussionsgrundlage: Sie helfen dabei, die zukünftige Entscheidung über die Beibehaltung oder Aufhebung der 50 + 1-Regel stakeholderorientiert zu beurteilen.